Perancangan Prototype Aplikasi Pembelajaran Budaya Batak Menggunakan Metode Web Based Learning (WBL) - Kristian Siregar (JUKI : Jurnal Komputer dan Informatika, 2019)
The influence of the development of information and communication technology has an impact on the educational aspect. One implementation of the development of information and communication technology (ICT) is web based learning (WBL). In addition, conventional and classical learning methods require teachers to use media that are relevant to the demands of the times so that students are motivated in learning Batak culture. interesting and to learn according to the behavior or characteristics of students. Referring to its dynamic nature, learning content can be updated and does not close the possibility of being developed for subjects in the future. In this study, the research and development model of the dick and carey teaching system design model. The model has the following steps: identifying learning objectives, analyzing teaching, recognizing student behavior and characteristics, formulating information objectives developing benchmark points of reference, selecting and developing teaching materials, designing and conducting formative assessments, revising teaching.